Think strategically - Gimbert, Xavier (Houndmills, Basingstoke, Hampshire ; New York : Palgrave MacMillan, 2011)
'If you think more strategically than your competitors, your company will win the competitive battle in the mid or long term. This book explains simply and clearly the elements, concepts, analyses and interrelationships that make up this strategic thinking, and shows how to employ it in your business or organization'--
Machine generated contents note: -- Introduction -- Strategic Management -- Strategic Levels and Processes -- Key Strategic Concepts -- Competitive Advantage and Strategy -- Macro-environment -- PEST Analysis, Types of Environment and Scenarios -- Industry -- Levels and Definitions -- Industry (II) -- Micro, Strategy, Strategic Dimensions and Groups -- Market -- Segments, Key Success Factors and Minimum Success Factors -- Resources and Capabilities -- Key Result Areas, Core Competences -- Industry Value Chain -- Distributing and Changing Value -- Company Value Chain -- Core Activities, Strategy, Outsourcing and other Perspectives -- Globalisation and Strategy -- Strategy and Crisis -- The Strategic Core as a Management Model in the Face of Complexity -- Guide to Book Chapters through the GIB Model -- Acknowledgements -- Figures.
Includes bibliographical references and index.
Keywords: Strategic planning